Attention for action in visual working memory. (October 2020) - Olivers, Christian N.L.; Roelfsema, Pieter R.
Abstract: From the conception of Baddeley's visuospatial sketchpad, visual working memory and visual attention have been closely linked concepts. An attractive model has advocated unity of the two cognitive functions, with attention serving the active maintenance of sensory representations. However, empirical evidence from various paradigms and dependent measures has now firmly established an at least partial dissociation between visual attention and visual working memory maintenance – thus leaving unclear what the relationship between the two concepts is. Moreover, a focus on sensory storage has treated visual working memory as a reflection of the past, with attention as a limiting resource. This view ignores what storage is for: immediate or future action. We argue that rather than serving sensory storage, attention emerges from coupling relevant sensory and action representations within working memory. Importantly, this coupling is bidirectional: First, through recurrent feedback mechanisms, action coupling results in the enhancement of the appropriate sensory memory representation. Under this view, unattended memories are currently not coupled to an action plan, but are not necessarily lost and remain available for future tasks when necessary. Second, through the very same feedback projections, attention serves as the credit assignment mechanism for the action's outcome. When the action is successful, the associated representations are being reinforced, leading to more robust consolidation and more rapid retrieval in the future – thus explaining performance benefits for attended memories without assuming that attention serves as the maintenance mechanism. By firmly grounding VWM in the action system, the new framework integrates a range of behavioural and neurophysiological findings and avoids circularity in explaining the role of attention in working memory.